Review Buku Islam di Tanah Jawa Abad XIII-XVI: Pribumisasi Islam dan Dekolonisasi Sejarah Umat Islam - Hasan Basri Marwah (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
“Tend to see all pasts through [the] creedal difference” (Manan Abdul Asif, 2016: 4) “Because we are non-Western people from a civilization that has always been in conflict with the West. The world of Islam has always been a historical competitor, and it has never capitulated” (Edward Said, 2002: 288)